Comparative study on the synthesis of magnetic ferrite adsorbent for the removal of Cd(II) from wastewater - Fang Liu; Kanggen Zhou; Quanzhou Chen; Aihe Wang; Wei Chen (Adsorption Science & Technology)
The magnetic ferrites were synthesized at ambient temperature through the precipitation method in aqueous solution at varying pH values and were used as novel adsorbents for heavy metal-containing wastewater treatment. The magnetic ferrites were applied for the removal of Cd(II) ion from wastewater. The synthesized magnetic ferrites were characterized by settling velocity, X-ray diffraction, scanning electron microscopy, laser particles size analyzer, and vibrating sample magnetometer. The effects of pH value and contact time on the adsorption process were investigated. The magnetic ferrites had a saturation magnetization value of 82.30 emu/g and a settling velocity of 2%, indicating easy separation from aqueous solution under magnetic field. The adsorption of Cd(II) onto the magnetic ferrites followed the pseudo-second-order kinetics and the Langmuir isotherm model. The most suitable pH condition for the synthesis of magnetic ferrite with optimal Cd(II) adsorption capacity was 9.0, and a maximum adsorption capacity of 160.91 mg/g for Cd(II) ions can be achieved. Based on the cost analysis, the magnetic ferrite was a cost-effective adsorbent for Cd-containing wastewater treatment.